MENILAI AKSESIBILITAS AIR MINUM (STUDI KASUS: AKSESIBILITAS AIR BERSIH BAGI MASYARAKAT MISKIN DI KOTA SEMARANG) - Maryono, Maryono (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2007)
Water  accesibility    for  the  poor  people  is  one  of  the  indicator  on  water  supply  and delivary sistem in the cities. Batram and Howard have make a catagorization for the accessibility. There are three level; law accessibility, medium accessibility and hight accessibility. The Accessibility in Semarang City for is at the medium. But the people must spent 5 % from the revenue every month to acces the water. This situation is bad, regarding of the standart, the should spent not more then 3 %.